"Because It's Hers": When Preschoolers Use Ownership in Their Explanations. (3rd March 2016) - Nancekivell, Shaylene E.; Friedman, Ori
Abstract: Young children show competence in reasoning about how ownership affects object use. In the present experiments, we investigate how influential ownership is for young children by examining their explanations. In three experiments, we asked 3‐ to 5‐year‐olds ( N  = 323) to explain why it was acceptable (Experiments 1–3) or unacceptable (Experiment 2 and 3) for a person to use an object. In Experiments 1 and 2, older preschoolers referenced ownership more than alternative considerations when explaining why it was acceptable or unacceptable for a person to use an object, even though ownership was not mentioned to them. In Experiment 3, ownership was mentioned to children. Here, younger preschoolers frequently referenced ownership when explaining unacceptability of using an object, but not when explaining why using it was acceptable. These findings suggest that ownership is influential in preschoolers' explanations about the acceptability of using objects, but that the scope of its influence increases with age.